Avoiding the Extremes of Life - Levy, David J. (Tufts Archival Research Center, 2006)
David Levy, Deputy District Attorney of Contra Costa County in California, describes how he learned level-headed contentment in order to survive as a POW on the Death March of Bataan during WWII.